Sosialisasi dan penyusunan Raperda Pendidikan Dasar di Kabupaten Pesisir Selatan - Aep Saefullah; Fahri Fahri; Devid Putra Arda; Ahmad Fadli; Joned C Saksana; Moeljono Moeljono (ABDIMAS DEWANTARA, 2023)
Pengabdian masyarakat ini bertujuan untuk mewujudkan regulasi dan peraturan tentang penye-lenggaraan dan pengelolaan Pendidikan dasar di Kabupaten Pesisir Selatan serta memberikan wawasan pemahaman kepada 240 tenaga pendidiik di lingkup Dinas Pendidikan Kabupaten Pesisir Selatan. Hasil dari kegiatan pengabdian masyarakat antara lain terwujudnya Rancangan perda tentang pengelolaan dan penyelenggaraan pendidikan dasar di Kabupaten Pesisir Selatan, masyarakat setuju dengan Perda Penye-lenggaraan dan Pendidikan Dasar, Perlu segera disahkan agar menjadi payung hukum dalam tata kelola pendidikan dasar serta dapat meningkatkan mutu pendidikan.   Socialisation and drafting of a draft Regulation on Basic Education in Pesisir Selatan District   Abstract: This community service aims to realize regulations and regulations regarding the implementation and management of basic education in Pesisir Selatan districts and provide insight into understanding 240 education personnel within the scope of the South Coast District Education Office. The results of community service activities include the realization of a draft bylaw on the management and implementation of basic education in Pantai Selatan District. The community agrees with the Regional Regulation on the Implementation and Basic Education. It needs to be passed immediately so that it becomes a legal umbrella in basic education governance and can improve the quality of education.